Resilience to discrimination stress across ethnic identity stages of development. Issue 1 (3rd December 2013) - Romero, Andrea J.; Edwards, Lisa M.; Fryberg, Stephanie A.; Orduña, Michele
Abstract Ethnic identity development may increase resilience to discrimination and prejudice, which are often common and stressful for ethnic minority adolescents. Based on ethnic identity development theory and resilience theory, we hypothesize that under high discrimination stress, ethnic affirmation and ethnic identity stage will have protective moderating effects on self‐esteem and depressive symptoms. A cross‐sectional self‐report study with 125 ethnic minority adolescents (13–18 years) found that ethnic affirmation (p < .05) had protective effects on depressive symptoms (p < .05) and protective‐enhancing effects on self‐esteem at high levels of discrimination stress. Achieved ethnic identity stage (p < .05) had protective‐stabilizing effects on self‐esteem at high discrimination stress. Our findings demonstrate that the protective elements of ethnic identity are feeling positive about one's ethnic group, having learned about one's history, and having resolved conflicts about one's ethnic group.